CUSTOMER TRUST AND EXPERIENCE AS DRIVERS OF CUSTOMER LOYALTY: A CASE STUDY OF GARUDA INDONESIA IN SELATPANJANG CITY - Darimi, Darimi (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2024)
Customer loyalty plays a crucial role in a company's success by fostering repeat purchases and brand advocacy. This study examines the influence of customer trust and experience on customer loyalty, focusing on Garuda Indonesia customers in Selatpanjang City. Data collection was conducted using a Likert scale questionnaire, and analysis employed multiple linear regression to evaluate the effects of trust and experience on loyalty. The findings indicate that customer trust and experience have a significant simultaneous effect on loyalty, with trust emerging as the more dominant factor. However, customer experience does not independently influence loyalty. To strengthen loyalty, Garuda Indonesia should continue enhancing service quality to ensure customer satisfaction and cultivate positive perceptions of its brand. Keywords: Customer Loyalty, Customer Trust, Customer Experience, Airline Industry, Service Quality